Current Concepts and Pitfalls in the Management of Obstructive Sleep Apnea. (23rd August 2013) - Pang, Kenny P.; Rotenberg, Brian; Woodson, B. Tucker
Abstract : Program Description: There are many different ways and surgical techniques available to treat OSA, causing a lot of confusion and disparity in managing these OSA patients. There is a need to standardize diagnosis, treatment, and prognosis. Concepts will be discussed and pitfalls will be highlighted. This miniseminar will address these latest current concepts in airway evaluation, clinical diagnosis, polysomnographic diagnosis, and various surgical management (from nose, palate, and tongue surgery). The miniseminar will also highlight the pitfalls that should be avoided in the management of OSA. Educational Objectives: 1) Recognize the basic concepts of airway evaluation and diagnosis and surgical management of OSA. 2) Confidently diagnose, evaluate, and treat patients with OSA.